Communication and safe and effective nursing care in surgical center and intensive care: integrative review - Marlene da Silva Miranda; Francisco Anderson Abreu do Nascimento; Viviane Nayara de Oliveira Lima; Francisco Jandson de Albuquerque; Ana Luiza Gonçalves da Silva; Andresa de Araújo Sales; Lucas Manoel Oliveira Costa; Nanielle Silva Barbosa (Hospital de Clínicas de Itajubá, 2023)
Objective: To identify the importance of communication for safe and effective nursing care in the surgical center and intensive care. Methods: An integrative review with a survey of productions in February 2023 in the databases Lilacs, MEDLINE, CINAHL, and Scopus. Primary studies, available in full in English, Portuguese, and Spanish, were included. Results: Of the 1,904 productions initially found, 19 were included for analysis. The studies pointed out that communication is essential to guaranty patient safety and to insert the family in the care process. This skill goes beyond verbal expression and involves other ways of communicating. However, it needs to be improved in some situations, mainly to avoid damage to the customer. It is also suggested that some forms of communication require to be standardized. Conclusion: Communication is one of the priorities and fundamental actions for the safety and effectiveness of nursing care, whether in surgical centers or intensive care units. Given this context, it is necessary that communication barriers are identified and that strategic organizational actions are put into practice, including the permanent education of professionals and the standardization of information. Actions like these minimize the potential risks that permeate critical care and positively impact relationships in the work environment.